Identifying the relation between feedback preferences and performance. Issue 2 (13th January 2021) - Bacotti, Janelle K.; Grauerholz‐Fisher, Emma; Morris, Samuel L.; Vollmer, Timothy R.
Abstract : Performance feedback is a common organizational behavior management intervention (Gravina et al., 2018) that typically yields consistent effects when combined with other procedures (Alvero et al., 2001). A noteworthy characteristic that might affect feedback effectiveness is timing (Lechermeier & Fassnacht, 2018). Given the frequent use and practical utility of feedback, we assessed feedback preference across three feedback timing options: after step, after trial, and after session. We used a direct‐choice paradigm to assess feedback timing preferences with undergraduate students completing two multistep computerized tasks. The data obtained suggest that most participants shifted their preference from relatively proximal (e.g., after step) to distal feedback (e.g., after session) as they acquired the tasks. A few participants' preferences varied despite increases in performance. We discuss implications based on the current findings and future directions for research.